Update on Animal Models of Exfoliation Syndrome. Issue 7 (July 2018) - Anderson, Michael G.; Meyer, Kacie J.; Hedberg-Buenz, Adam; Fingert, John H.
Abstract : Animal models are powerful tools for studying diseases that affect the eye, such as exfoliation syndrome (XFS). Two types of animal models have been used to investigate the pathophysiology of XFS and glaucoma. One class of models is engineered to have key features of a disease by alteration of their genome (genotype-driven animal models). LOXL1 is the first gene known to increase the risk for developing XFS in humans. Two transgenic mouse models with altered Loxl1 genes have been generated to study XFS. One strain of mice, Loxl1 deficient mice, also known as Loxl1 knockout mice, have had the Loxl1 gene removed from their genomes. Another strain has been engineered to produce excess amounts of the protein produced by the Loxl1 gene, or Loxl1 overexpression. A second class of animal models includes naturally occurring strains of mice that exhibit key clinical features of a disease. Studies of these phenotype-driven animal models may identify genes that cause disease and may also provide a valuable resource for investigating pathogenesis. One strain of mice, B6- Lyst bg-J, has several key features of human XFS, including ocular production of exfoliation-like material, and stereotypical iris abnormalities. Studies of this range of mice and other public mouse genetic resources have provided some important insights into the biology of XFS and may be useful for future studies to test the efficacy of drug therapies.